2001
DOI: 10.1034/j.1399-3054.2001.1120405.x
|View full text |Cite
|
Sign up to set email alerts
|

Response of the cultivated tomato and its wild salt‐tolerant relative Lycopersiconpennellii to salt‐dependent oxidative stress: The root antioxidative system

Abstract: The response of the antioxidant system to salt stress was studied in the roots of the cultivated tomato Lycopersicon esculentum Mill. cv. M82 (Lem) and its wild salt-tolerant relative L. pennellii (Corr.) D'Arcy accession Atico (Lpa). Roots of control and salt (100 mM NaCl)-stressed plants were sampled at various times after commencement of salinization. A gradual increase in the membrane lipid peroxidation in salt-stressed root of Lem was accompanied with decreased activities of the antioxidant enzymes: super… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
194
4
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 395 publications
(239 citation statements)
references
References 53 publications
32
194
4
1
Order By: Relevance
“…DHA undergoes irreversible hydrolysis to 2, 3-diketogulonic acid or is recycled to AsA by DHAR, thereby capturing AsA before it lost. Recent studies showed that both MDHAR and DHAR are equally important in regulating AsA levels and its redox state under oxidative stress condition (Eltayeb et al 2006(Eltayeb et al , 2007Wang et al 2010;Shalata et al 2001). Results obtained in this study showed that both MDHAR and DHAR decreased along with a decreased level of AsA (Figs.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…DHA undergoes irreversible hydrolysis to 2, 3-diketogulonic acid or is recycled to AsA by DHAR, thereby capturing AsA before it lost. Recent studies showed that both MDHAR and DHAR are equally important in regulating AsA levels and its redox state under oxidative stress condition (Eltayeb et al 2006(Eltayeb et al , 2007Wang et al 2010;Shalata et al 2001). Results obtained in this study showed that both MDHAR and DHAR decreased along with a decreased level of AsA (Figs.…”
Section: Discussionsupporting
confidence: 58%
“…Along with its oxidized form (GSSG), it acts as a redox couple important for maintaining the cellular homeostasis, playing a key role in diverse signaling systems in plants (Noctor 2006). Furthermore, GSH plays a protective role in salt tolerance by maintaining the redox state (Shalata et al 2001). The increased level of the GSH pool is generally regarded as a protective response against oxidative stress (May and Leaver 1993;Xiang and Oliver 1998), although defense against stress situations sometimes occurs irrespective of the GSH concentration (Potters et al 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, a degree of cellular oxidative damage in plants resulting from abiotic stress is mediated . It has been reported that salinity tolerance is closely related to antioxidant capacity in many plant species (Gossett et al 1994;Hernandez et al 1995;GuetaDahan et al 1997;Dionisio-Sese and Tobita 1998;Meneguzzo et al 1999;Hernandez et al 2000;Sreenivasulu et al 2000;Shalata et al 2001;Bor et al 2003;Mittova et al 2003;Turkan 2004, 2005;Koca et al 2006Koca et al , 2007Sekmen et al 2007;Yazici et al 2007;). In addition, transgenic plants overexpressing ROS-scavenging enzymes such as SOD (Badawi et al 2004;Tseng et al 2007), CAT (Tseng et al 2007), APX (Wang et al 1999) and GR (Foyer et al 1995) showed enhanced tolerance to the oxidative stresses in plants under adverse conditions.…”
Section: Oxidative Stress Induced By Salt Stressmentioning
confidence: 99%
“…Prx IIB mRNA levels increase slightly after 6-8 h and Prx IIC mRNA levels increase dramatically within 2 h in response to 50 mM NaCl treatment in Arabidopsis [6]. Salinity causes oxidative stress, and salt tolerance is related to the induction of antioxidant defenses [25]. UV irradiation can cause oxidative stress by generating ROS in plants [26], which leads to oxidative damage.…”
Section: Discussionmentioning
confidence: 99%